Limits of the current consensus on development: keynote address - Patel, I.G. ([s.n.] [S.l.], 1993)
Draws attention to the limits of current consensus by warning against three dangers viz.: oversimplification with reference to some areas of economic policy; excessive expectations from economic policies; and neglecting a number of important questions which are beyond economic policy and which are yet crucial for growth and poverty eradication e.g. technology. Points out that these dangers are real and have a bearing on the conduct of international economic relations.